An empirical study on information technology enabled services enterprises in India. (1st January 2014) - Mahadevan, Dhanashree; Subash Babu, A.; Ramanathan, A.
The story of the Indian IT and ITES firms has been an interesting one for the world community. The phenomenal success achieved by these firms created considerable interest among policy makers, researchers, educators, entrepreneurs, etc. The research reported in this paper pertains to a study carried out on Indian information technology (IT) and information technology enabled services (ITES) enterprises. For this, the necessary data was collected from the PROWESS database of Centre for Monitoring Indian Economy (CMIE). The data collected was subjected to a series of analysis to get a better insight about the performance of these companies. The details of the data collected, the analyses carried out, the results and the inference obtained are presented in this paper. In order to bring out some of the unknown facts about these firms, the firms were classified with the help of a novel method. After effecting the classification, further analysis was carried out using the method of ANOVA to identify the factors that are responsible for certain behaviour observed during the analysis. These details are also presented in this paper.